Do women, men, and companies related to economics use X in the same way? - Marcos Antón-Renart; Esther Ortiz-Martínez; Salvador Marín-Hernández (Heliyon)
The unquestionable importance of social networks as a means of communication in the 21st century leads us to analyze the behavior of a sample of X accounts representing people and firms who have shown a link with the world of economics at an international level. We analyze these agents in-depth and their behavior in this social network. We conclude that significant differences exist in how women, men, and companies interact on X. The information the accounts provide in their biography and the most used hashtag is also revealing. The results show some tips that will help use an X account, depending on whether the user is legal or natural. They show the reality of their accounts and how they use them. These results are helpful for professionals and policymakers as a departure point for looking for solutions that can be learned from others to increase the popularity or impact of their accounts.